HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN BAYI USIA 3-6 BULAN DI WILAYAH KERJA PUSKESMAS BANGKINANG - dita puteri, ade (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Exclusive breastfeeding in Indonesia has only reached 15.3%, while in Bangkinang Health Center exclusive breastfeeding is only 19.84%. This study aims to determine the relationship of exclusive breastfeeding with the development of 3-6 months old infants in the Bangkinang Community Health Center work area in 2018. The design of this study was analytic observational with a cross sectional approach. The population of this study were all infants aged 3 months - 3 months 15 days and 6 months - 6 months 15 days registered at the posyandu in the work area of the Bangkinang Health Center. The sampling technique was total sampling, totaling 51 babies. The study was conducted on 30 June to 13 July 2018, with the instrument in the form of a Development Pre-Screening Questionnaire. Data analysis used was Univariate and Bivariate, with Chi-Square test. The results showed that the distribution of exclusive breastfeeding at Bangkinang Public Health Center was 29.4% and the developmental distribution of infants aged 3-6 months according to the development stage was 41.2%. Based on the Chi-Square test results obtained P value (0.007) <Î± (0.05), there is a significant relationship between exclusive breastfeeding with the development of 3-6 months old infants in the Bangkinang Community Health Center working area in 2018. It is hoped that for the Puskesmas in order to provide information about the role of Exclusive Breastfeeding in the development of infants.